2020
DOI: 10.1038/s41591-020-0781-z
|View full text |Cite
|
Sign up to set email alerts
|

A soluble phosphorylated tau signature links tau, amyloid and the evolution of stages of dominantly inherited Alzheimer’s disease

Abstract: E.M. designed the study and wrote the initial draft of the manuscript. All authors collected samples and data, helped to interpret the results and reviewed drafts of the manuscript.Competing interests R.J.B. has equity ownership interest in C2N Diagnostics and receives royalty income based on technology (stable isotope labeling kinetics and blood plasma assay) licensed by Washington University to C2N Diagnostics. R.J.B. receives income from C2N Diagnostics for serving on the scientific advisory board. Washingt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
423
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 422 publications
(510 citation statements)
references
References 66 publications
47
423
5
Order By: Relevance
“…However, if plasma amyloid-β assays ( Ovod et al , 2017 ; Nakamura et al , 2018 ) are shown to reliably indicate amyloidosis then our data suggest that a blood test alone could be effective for screening for inclusion in trials seeking to reduce tau accumulation rates among cognitively unimpaired individuals. More recently plasma phosphorylated tau assays have been shown to correlate well with tau PET in vivo ( Mielke et al , 2018 ; Barthelemy et al , 2020 ; Karikari et al , 2020 ; Thijssen et al , 2020 ) and with Alzheimer’s disease pathology at autopsy ( Thijssen et al , 2020 ). These studies suggest, but do not prove, that plasma measures could be prognostic of tau accumulation rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, if plasma amyloid-β assays ( Ovod et al , 2017 ; Nakamura et al , 2018 ) are shown to reliably indicate amyloidosis then our data suggest that a blood test alone could be effective for screening for inclusion in trials seeking to reduce tau accumulation rates among cognitively unimpaired individuals. More recently plasma phosphorylated tau assays have been shown to correlate well with tau PET in vivo ( Mielke et al , 2018 ; Barthelemy et al , 2020 ; Karikari et al , 2020 ; Thijssen et al , 2020 ) and with Alzheimer’s disease pathology at autopsy ( Thijssen et al , 2020 ). These studies suggest, but do not prove, that plasma measures could be prognostic of tau accumulation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on familial AD patients have shown that the site-specific phosphorylation state of tau changes in different periods of disease progression [147]. Some sites are phosphorylated (e.g., formation of pTau217 and pTau181) as early as two decades before the development of aggregated tau-pathology.…”
Section: Tau Isoforms Domain Structure Post-translational Modificatmentioning
confidence: 99%
“…The finding that Tau becomes aggregated into amyloid filaments in AD and appears hyperphosphorylated triggered an extended search for kinases and phosphatases responsible for Tau's pathological state [reviews, (Martin et al, 2013, Hoffman et al, 2017], as well as searches for P-sites on Tau (Hanger, 2020), and treatments based on these results (Schneider and Mandelkow, 2008). The aim was to identify P-sites as early indicators of pathology in brain tissue, CSF, or in blood (Barthelemy et al, 2020, and as indicators of vulnerable brain circuits affected during Braak stages (Arnsten et al, 2019). In spite of this progress, the relationship between Tau's phosphorylation and aggregation remains enigmatic in view of its exceptional solubility.…”
Section: Significance Of Tau Phosphorylation In Ad Researchmentioning
confidence: 99%